Sifat Fisis Tanah Akibat Penambahan Serbuk Ampas Tahu - Athaya Zhafirah; Khoerul Mufti Ali (Jurnal Konstruksi, 2026)
Tofu dregs waste is an organic waste with high fiber content that has the potential to be used as a soil stabilization material. This study aims to evaluate the effect of tofu dregs powder addition on the physical properties of clay soil, especially in the context of geotechnics and infrastructure construction. The experimental method was conducted by mixing clay soil with tofu bagasse waste in varying proportions of 0 percent, 20 percent, 60 percent, and 80 percent of the dry weight of the soil. Tests included moisture content, content weight, specific gravity, sieve analysis, and Atterberg limits. The results showed that the addition of 80 percent tofu waste decreased the moisture content from 78.81 percent to 26.34 percent, decreased the plasticity index from 132 percent to 0 percent, and increased the content weight from 1.53 g/cm³ to 1.56 g/cm³. These results indicate that tofu waste is able to reduce the plasticity and moisture of clay soils, thus potentially improving soil stability as a base material for construction. This research shows that tofu waste can be a sustainable alternative solution for soil stabilization in geotechnical projects.